Agrohydrobusiness in the Chaco Region of Argentina (Salta, Santiago del Estero and Córdoba) - Toledo-López, Virginia Belén (2023)
In Argentina, the provinces of Córdoba, Salta and Santiago del Estero are cases of great importance in the context of agribusiness expansion, due to the spectacular loss of biodiversity, the frequent territorial conflicts carried out by indigenous peoples and peasants and, more recently, against the use of agrochemicals and their consequences on human and non-human health. This article aims to make visible some of the emerging experiences in the territories under study as transition initiatives, with special emphasis on the construction of resistances and alternatives.To this end, we address the main irruptions of agribusiness in the Chaco's web of life (understood as agrohydrobusiness, given the centrality assumed by the dispute over water resources in this region), considering its territorial, environmental and health consequences, to then analyze the main forms assumed by resistances and re-existences. The methodological proposal focuses on simultaneous work with different information construction and analysis techniques, such as: systematization and analysis of multiple secondary sources (journalists, statistics, legislation, reports from state and/or private organizations, among others), along with field records and in-depth interviews.